Doctors, families and the industry in the clinic: the management of 'intersex' children in Swiss paediatric medicine (1945–1970). Issue 3 (July 2021) - Janett, Mirjam; Althaus, Andrea; Hulverscheidt, Marion; Gobet, Rita; Streuli, Jürg; Condrau, Flurin
Abstract: This manuscript investigates clinical decisions and the management of 'intersex' children at the University Children's Hospital Zurich between 1945 and 1970. This was an era of rapid change in paediatric medicine, something that was mirrored in Zurich. Andrea Prader, the principal figure in this paper, started his career during the late 1940s and was instrumental in moving the hospital towards focusing more on expertise in chronic diseases. Starting in 1950, he helped the Zurich hospital to become the premier centre for the treatment of so-called 'intersex' children. It is this treatment, and, in particular, the clinical decision-making that is the centre of our article. This field of medicine was itself not stable. Rapid development of diagnostic tools led to the emergence of new diagnostic categories, the availability of new drugs changed the management of the children's bodies and an increased number of medical experts became involved in decision-making, a particular focus lay with the role of the children themselves and of course with their families. How involved were children or their families in an era widely known as the golden age of medicine?